1995
DOI: 10.1037/1196-1961.49.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Attributions of Fluency in Fame Judgments by Younger and Older Adults.

Abstract: Judgments about stimulus characteristics are affected by enhanced processing fluency that results from an earlier presentation of the stimulus. By monitoring for an episodic source of processing fluency, younger adults can more easily avoid this influence than can older adults. In Experiment 1, older adults discounted the effects of fluency when task demands encouraged the use of analytic judgments based on general knowledge, rather than an appeal to episodic source monitoring. Younger subjects were not reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(50 reference statements)
0
3
1
Order By: Relevance
“…Following this reasoning, all potential outcomes of a study can be post hoc explained by motivation. Clearly, without an explanation why participants were motivated to discount fluency in other studies (Bornstein & D'Agostino, 1994;Masson, et al, 1995;Oppenheimer, 2004;O'Brien, 2013) but not in the present study, motivation is insufficient to explain the outcome of the present experiments.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Following this reasoning, all potential outcomes of a study can be post hoc explained by motivation. Clearly, without an explanation why participants were motivated to discount fluency in other studies (Bornstein & D'Agostino, 1994;Masson, et al, 1995;Oppenheimer, 2004;O'Brien, 2013) but not in the present study, motivation is insufficient to explain the outcome of the present experiments.…”
Section: Discussioncontrasting
confidence: 68%
“…This outcome is clearly inconsistent with the overdiscounting hypothesis, which predicts that participants who are aware of sources of fluency that are not diagnostic of their judgment will overdiscount this fluency (e.g., Oppenheimer, 2006). Several authors have used discounting to explain the reduction, elimination, or reversal of fluency effects (e.g., Bornstein & D'Agostino, 1994;Masson, Carroll, & Micco, 1995;Oppenheimer, 2004;O'Brien, 2013). However, if discounting can account for almost every possible data pattern, it needs more refinement as a concept.…”
Section: Discussionmentioning
confidence: 84%
“…In this case, the prepotent response tendency would be to interpret familiarity as fame. More generally, in situations where the potential for confusion is high, the individual would have to inhibit a salient response, i.e., based perhaps on perceptual fluency, in order for appropriate metacognitive judgments to occur (see also, Diamond, 1990;Jennings & Jacoby, 1993;Masson, Carroll, & Micco, 1995;Moscovitch, 1994;Shimamura, Jurica, Mangels, Gershberg, & Knight, 1995). The inhibitory regulation hypothesis (Hasher & Zacks, 1988) provides a similar formulation except that the role of inhibitory control as a gate to working memory is emphasized.…”
Section: Behavioral Source Memory Paradigmsmentioning
confidence: 99%
“…It has also been demonstrated that despite age differences in explicit memory for source, older adults benefit at least as much as younger adults when the perceptual characteristics of the stimuli are reinstated at test (Naveh-Benjamin & Craik, 1995). Moreover, reducing the degree to which perceptual fluency would be used as a basis for source monitoring decisions can eliminate age-related differences in source error (Multhaup, 1995;Masson, Carroll, & Micco, 1995). Thus, there is some evidence that older adults encode enough information to inform source judgements but that they are unlikely to use this information when self initiated, online monitoring is required or when the task allows dependence on a fluency heuristic.…”
Section: Accounting For Source Errormentioning
confidence: 99%